Study on the Development of Embryo and Larva of the Humpback Grouper (Cromileptes Altivelis Valencee) and its Feeding Behaviour - Bulanin, Usman (2002)
A series of experiments were conducted to determine 1) the embryonic and larval development, 2) feeding performance and 3) weaning of humpback grouper, Cromileptes altivelis, larva. The above study was carried out from spawning of broodstocks to obtain the fertilized eggs till they hatched. The results showed that the mean diameter of humpback grouper egg was 828.69 ± 45.91 um. The fertilized eggs hatched in 20 hour 10 minutes at the temperature of 27 to 28°C. The hatched larvae had a mean length of 1.86 mm, and a mean height of 0.460 mm. The yolk sacs and oil droplets were totally utilized after 63 and 65 hour after hatching (HAH), respectively. Within one day, the larvae had an average length and height of 2.253 mm and 0.615 mm, respectively. At 49 DAH, the mean length and height increased to 27.153 mm and 9.190 mm respectively. The spines on the larvae began to appear at day 7 to day 1 0. The dorsal spines reached their maximum length at day 28 to day 30, and the spines had a maximum mean length of 5668.30 um, while the ventral spines had a maximum mean length of 4415.44 11m at day 25-28. Then the spines began to reduce and change to hard rays as the larvae grew. The eyes pigments started to be visible at day 3 to day 4 after hatching (DAH). The larvae's mouths were opened for the first time at day 2 or 45 HAH. The relationship of mouth gape and eyes diameter was quadratic with an equation of MG = -02E-05Ed2 + 0.3992Ed + 215.05 and R2 = 0.96. Appearance of black spots at the caudal peduncle, dorsal fin and anal fin occurred between day 25 to day 30. These spots would increase in numbers and would spread towards the head and became perfected at day 40 to day 45, and they would look similar to the juvenile fish. The teeth of humpback grouper fish larvae began to appear at day 15, but those teeth were still few in numbers and were short. The height and width of larvae teeth increased as the larvae grew. At day 30, the larvae teeth got closer with a mean height and width of 110.18 um and 40.13 um respectively. Histologically, no fold occurred in the larvae digestive tract yet before they reach 5 days old. The incipient stomach began to be visible at day 30. The larvae's stomachs were perfected at 45 DAH. The liver began to be visible at day 5, while the pancreas was visible at day 10. The protease enzyme activity increased as the larvae grew.